(untitled) (Al-Farooq Journal of Sciences, 2026)
The current research analyses the impact of public expenditure on the inflation rate in Libya economy ranging from 1970 to 2025, cointegration approach was adopted in this research by using Engel-Granger method, error correction method, and Engle causality to identify the impact of public expenditure on the inflation rate.. The study resulted that there is a positive impact of public expenditure on the inflation rate, and causal relationship between independent variable and dependent variable in the long and short term.